The bed of Procrustes : philosophical and practical aphorisms - Taleb, Nassim Nicholas, 1960- (Random House, 2010)
By the author of the modern classic The Black Swan, this collection of aphorisms and meditations expresses Taleb's view of modern civilization's hubristic side effects--modifying humans to satisfy technology, blaming reality for not fitting economic models, inventing diseases to sell drugs, defining intelligence as what can be tested in a classroom, and convincing people that employment is not slavery.